Diasporic Cosmopolitanism and Digital (Dis)Connectivity Among Turkish Women in Rome - Claudia Minchilli (Media and Communication)
This study advances the field of disconnection studies by examining how digital (dis)connective practices intersect with diasporic identity construction and the articulation of belonging, focusing on the experiences of Turkish migrant women in Rome. Based on in-depth interviews and participant observation with 10 Turkish women, the research highlights the central role of social class in the emergence of a “diasporic cosmopolitan” identity that is culturally and socially detached from, or even opposed to, their national identity. It further shows how this “cosmopolitan” identity intersects with the performance of specific digital (dis)connective practices and explores the cultural, political, and social dimensions of these dynamics. Particular attention is given to the influence of contemporary Turkish politics on online and offline diasporic sociality, which fosters tensions and segmented solidarities. Through this lens, the study identifies emergent forms of digital (dis)connective practices among Turkish women in Rome, which shape transnational and local social alliances and disruptions.